EFEKTIVITAS PROGRAM BPJS KESEHATAN DI KOTA SEMARANG (Studi Kasus pada Pasien Pengguna Jasa BPJS Kesehatan di Puskesmas Srondol) - Monica Pertiwi; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2017)
The Government is working to improve the quality of public health with the use of social security. Social security is one form of social protection organized by the government of useful guarantee citizens or communities to meet the basic necessities of life. One of them is through the health security program which is organized by the organizer of the social security (BPJS). BPJS health is a government program to meet the basic needs of life of the community in the field of health. The program is expected to serve and provide protection so that all people get access health equally. Based on the background of this research aims to know the effectiveness of the program BPJS in Semarang and inhibiting factors in the effectiveness of BPJS Health Program in the city of Semarang. This study used quantitative descriptive research type with a total sample of 98 patients who use the services BPJS Health at Public Health Center Srondol. This study uses five indicators to measure the effectiveness of programs that socialization program, program understanding, precision targeting, program objectives and real change. Based on data analysis, conclusion that the effectiveness of BPJS Health program in Semarang can be said to be effective. Based on the five indicators, which have the lowest level of effectiveness is an indicator socialization program that scores of 1.83 (less effective). Factors that are considered obstacles in the effectiveness BPJS program is socialization programs, services and dues BPJS.